Boosting Creativity through Digital Disruption? The Role of Co-Creation Platforms in the Media Production Field. (16th November 2016) - Monaci, Sara
Web technologies transformed the media production field in many aspects: audiovisual contents in particular, are at the centre of a reshaping process involving their use, creative production, distribution and consumption. The effects of digital disruption are revealed though a media production field characterized by an increasing complexity. Co-creation environments emerge as new digital intermediaries, which may integrate the open collaboration of peers with the need to identify new ways of recognising and enhancing creativity in a sustainable way. Based on an empirical analysis of seventy co-creation web platforms related to the audiovisual domain, the paper aims at identifying an organisational model for creative production whilst reflecting on the role of platforms such as Tongal, Userfarm, Filmaka and others amongst consolidated institutions such as the cultural industries and new technological players such as Netflix, Hulu, Amazon etc.